1992
DOI: 10.1111/j.1745-9125.1992.tb01105.x
|View full text |Cite
|
Sign up to set email alerts
|

School Bonding, Race, and Delinquency*

Abstract: While there is considerable evidence that blacks experience school in qualitatively distinct ways from whites, there has been a general failure to examine racial variation in the impact of school variables on juvenile misconduct. The purpose of this research is to describe the manner in which school bonding affects delinquent conduct, focusing in particular on the role of the school in the delinquent involvement of black youths. Our orientation is primarily a control theory one that suggests that the greater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
213
2
4

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(233 citation statements)
references
References 36 publications
14
213
2
4
Order By: Relevance
“…Results of the current study also support past studies that have shown that bonds to school are important factors in girls' delinquency (Anderson et al, 1999;Archwamety and Katsiyannis, 1998;Cernkovich and Giordano, 1992;Erickson et al, 2000;Hamalainen and Pulkkinen, 1995;Lewin et al, 1998;Rosenbaum and Lasley, 1990). The findings of this study underscore the need to examine school-related variables in the study of girls' delinquency.…”
Section: Discussionsupporting
confidence: 79%
“…Results of the current study also support past studies that have shown that bonds to school are important factors in girls' delinquency (Anderson et al, 1999;Archwamety and Katsiyannis, 1998;Cernkovich and Giordano, 1992;Erickson et al, 2000;Hamalainen and Pulkkinen, 1995;Lewin et al, 1998;Rosenbaum and Lasley, 1990). The findings of this study underscore the need to examine school-related variables in the study of girls' delinquency.…”
Section: Discussionsupporting
confidence: 79%
“…The four indicators of academic competence were self-reported school grades, and three indicators of attachment to and engagement in school, from Cernkovich and Giordano (1992): school orientation (seven items, sample item: "Schoolwork is very important to me," α=.82); school engagement (three items, sample item: "When you last attended school, how many hours a week did you usually spend doing homework? ", α=.43); and bonding to teachers (three items, sample item: "Most of my teachers treat me fairly," α=.66).…”
Section: Methodsmentioning
confidence: 99%
“…Emotional Engagement with School: Bonding: Students rated their emotional bonding with school on a 6-item, 5-point scale (1= strongly disagree, 5= strongly agree, Cernkovich & Giordano, 1992), e.g. "I feel I really belong at school."…”
Section: Emotional Engagement With Schoolmentioning
confidence: 99%